Enabling integration of internal data and external business information new technologies deliver accurate snapshots. - Purcell, Patti
Few executives will deny that critical business decisions must be based upon timely, accurate information. Historically, however, delivering action-able business intelligence to the appropriate person at the right moment has been difficult, largely due to the fact that internal corporate information commonly resides in isolated islands of information, with each functional area maintaining its own repository of data, with its own data taxonomy.